Implementasi Pendekatan Saintifik untuk Meningkatkan Kreativitas Belajar Siswa Mata Pelajaran Aqidah Akhlak - Aprilia Nur Laeli; Zakiyah Zakiyah (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to determine the implementation of a scientific approach to improve student learning creativity in the seventh grade Aqidah Morals subject at MTs Muhammadiyah 04 Slinga Purbalingga. This research includes qualitative descriptive research. Subjects were teachers of moral aqidah subjects and male students of class VII B at MTs Muhammadiyah 04 Slinga Purbalingga. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the study indicate that the implementation of a scientific approach to improve learning creativity starts from pre-learning activities (by making lesson plans). Then proceed with the activities of the learning process (steps of a scientific approach, learning resource media, and evaluation). The first problem faced in the learning process is that the teacher is accustomed to using the lecture method. The solution is that the teacher must change the lecture method into a varied method. The second problem faced is the lack of student interest in the subject of moral aqidah. The solution is that the teacher motivates students. The implementation of the scientific approach is able to increase student learning creativity with evidence that students are happy and enthusiastic about learning aqidah morality subjects and are able to increase student learning creativity. And the teacher is able to carry out the steps of a scientific approach well in the subjects of aqidah morals.